New species of the genus Amphinemura (Plecoptera: Nemouridae) from Yunnan, China - Du, Yu-Zhou; Wang, Zhi-Jie (Zootaxa, 2007)
Four new species, Amphinemura auriculata Du & Wang, sp. nov., A. dispositspina Du & Wang, sp. nov., A. hamatmicroda Du & Wang, sp. nov., and A. latifollicula Du & Wang, sp. nov. from Yunnan province, China are described in this paper.